A synergetic effect of an alkyl-thiophene π-bridge and side chain modification on device performances for stable all-polymer solar cells with high PCE. Issue 31 (25th July 2018) - Zhang, Tao; Feng, Wenhuai; Wang, Wen; Zhen, Hongyu; Chen, Peifeng; Ling, Qidan
Abstract : By incorporating a π-bridge and side chain modification, an ideal combination (PBDT(T)-HT-TPD/P(NDI2HD-Se)) was successfully obtained for all-PSCs with high PCE and excellent thermal-stability. Abstract : Tuning the structure of both polymer donors and acceptors, and development of novel matched donor/acceptor pairs are essential steps to enhance the power conversion efficiency (PCE) and stability of all-polymer solar cells (PSCs). Here, two weakly crystalline wide band-gap polymer donors PBDT(T)-HT-TPD and PBDT(ST)-HT-TPD with different side chains were synthesized by incorporating an alkyl-thiophene π-bridge, PBDT(T)TPD-based 2D-benzo[1, 2- b :4, 5- b ]dithiophene (BDT) and thieno[3, 4- c ]pyrrole-4, 6-dione (TPD) as reference donors. Three highly crystalline narrow-bandgap polymer acceptors P(NDI2OD-T), P(NDI2OD-Se) and P(NDI2HD-Se) sharing a similar backbone structure were also synthesized and studied. The all-PSCs were fabricated to investigate the synergetic effect of the alkyl-thiophene π-bridge and side chain modification. As a result, the PBDT(T)-HT-TPD/P(NDI2HD-Se) system is an optimal donor/acceptor combination due to its complementary light absorption and well-balanced miscibility/crystallinity, in which the highest power conversion efficiency (PCE) of 6.80% is achieved without extra-treatment. Meanwhile, the stability test of the devices shows that the incorporation of the alkyl-thiophene π-bridge can enhance thermal and storage stability. This work demonstrates that increasing the amorphous region of the donor to an appropriate degree provides an enhancement in the miscibility and morphology stability with highly crystalline acceptors, which will result in stable all-PSCs with high PCE.